The influence of date seed powder feeding on broiler performance (The Sudan Journal Of Animal Production المجلة السودانية للانتاج الحيواني, 2021)
The influence of date seed powder feeding on broiler performanceRehab S. M. Abdalla1, I. I. Hamid2, A.A. Hamza 2, M. A. Eltayeb3and A .M. El Hussein4 1Sudanese Nuclear and Radiological Regulatory Authority , Ministry of Higher Education  and Scientific Research – Sudan2Animal  Production Research Centre (Kuku) – Sudan3Sudan Atomic Energy Commission; Ministry of Higher Education and  Scientific   Research4Central Laboratory; Ministry of Higher Education and Scientific Research – SudanE-mail:  abdelhussein@hotmail.comE-mail:hamidnaile@hotmail.com Summary:This study was conducted during October and December 2020 at the Animal Production Research Centre (APRC) to assess the effects of dietary inclusion of date seed powder (DSP) on the performance of broiler chickens reared for 35 days of age. Ninety broiler chicks (Arber Acres Hybrid) were used in the experiment. Birds were divided into 3 equal groups (30 birds/group) replicated 3 times with 10 birds per replicate and were randomly allocated to the experimental diets. Three broiler diets were formulated according to the nutrients requirements as outlined by NRC (1994), diet 1 was control (0.0 DSP), diet 2 (1% DSP) and diet 3 (2% DSP). All Diets were isocaloric and isonitrogenous. Feed intake, body weight gain and feed conversion ratio were recorded weekly. Organoleptic test of chicken meat was conducted at the end of the experiment. The obtained data were statistically analyzed by one way ANOVA using SPSS 22 program. The results showed that the diets containing1 and 2 % DSP gave higher weight gains and better feed conversion compared to the control, however feed intake was significantly not affected. Furthermore, broilers meat of the group fed 2% DSP showed the best sensory evaluation, regarding color, flavor, odor, juiciness, tenderness and the overall acceptability compared to the control and those fed 1% DSP.It can be concluded that adding DSP up to 2 % in broiler diet will improve broiler performance and the taste of broiler meat. Keywords: date pits, broiler performance, panel test, final weight
Keywords: date pits; broiler performance; panel test; final weight; Alternative feed ingredients; Poultry nutrition; Body weight gain; Feed conversion ratio (FCR); Date seed powder (DSP)